Implementation of School Religious Activities in Forming Student Islamic Character Education - Maryam Fuji Ayu Renita (Elementaria: Journal of Educational Research, 2023)
This paper was created to describe the implementation of student character education through religious activities at SMK PGRI Jatibarang and to describe whether the implementation of school religious activities can shape the Islamic character of SMK PGRI Jatibarang students. This research was conducted using qualitative methods with case studies at SMK PGRI Jatibarang. The data collection techniques used by researchers are interviews, observation, and documentation. However, because a pandemic that is currently sweeping the world. Researchers focused more on research by using interviews with primary data sources, namely school principals and students, and secondary data sources, namely teachers and school staff. The first conclusion from this study is that character education cannot only be applied through learning but can be implemented through religious activities in schools. The second is, by using the habituation method carried out at school, SMK PGRI Jatibarang has so far been successful in carrying out the school programs that have been planned. In the implementation process, the SMK PGRI Jatibarang school always provides support to its students, so that the implementation of Islamic character education through habituation can go according to plan.